Salsalate ameliorates metabolic disturbances by reducing inflammation in spontaneously hypertensive rats expressing human C-reactive protein and by activating brown adipose tissue in nontransgenic controls - Trnovská, Jaroslava; Šilhavý, Jan; Kuda, Ondřej; Landa, Vladimír; Zídek, Václav; Mlejnek, Petr; Šimáková, Miroslava; Strnad, Hynek; Škop, Vojtěch; Oliyarnyk, Olena; Kazdová, Ludmila; Haluzík, Martin; et al. (PloS one, 2017)
Chronic low-grade inflammation plays an important role in the pathogenesis of insulin resistance. In the current study, we tested the effects of salsalate, a non-steroidal anti-inflammatory drug, in an animal model of inflammation and metabolic syndrome using spontaneously hypertensive rats (SHR) that transgenically express human C-reactive protein (SHR-CRP rats). We treated 15-month-old male transgenic SHR-CRP rats and nontransgenic SHR with salsalate (200 mg/kg/day) mixed as part of a standard diet for 4 weeks. A corresponding untreated control group of male transgenic SHR-CRP and SHR rats were fed a standard diet without salsalate. In the SHR-CRP transgenic strain, salsalate treatment decreased circulating concentrations of the inflammatory markers TNF-α and MCP-1, reduced oxidative stress in the liver and kidney, increased sensitivity of skeletal muscles to insulin action and improved tolerance to glucose. In SHR controls with no CRP-induced inflammation, salsalate treatment reduced body weight, decreased concentrations of serum free fatty acids and total and HDL cholesterol and increased palmitate oxidation and incorporation in brown adipose tissue. Salsalate regulated inflammation by affecting the expression of genes from MAPK signalling and NOD-like receptor signalling pathways and lipid metabolism by affecting hepatic expression of genes that favour lipid oxidation from PPAR-α signalling pathways. These findings suggest that salsalate has metabolic effects beyond suppressing inflammation.
Keywords: játra; Oxidative Stress; metabolismus lipidů; kyseliny mastné neesterifikované; oxidační stres; salicylany; Humans; C-reaktivní protein; Lipid Metabolism; Insulin Resistance; Hypertension; NLR Proteins; geneticky modifikovaná zvířata; PPAR alpha; Salicylates; Inflammation; krysa rodu Rattus; lidé; zvířata; zánět; metabolický syndrom; hnědá tuková tkáň; NLR proteiny; TNF-alfa; Animals, Genetically Modified; Liver; inzulinová rezistence; hypertenze; Metabolic Syndrome; Fatty Acids, Nonesterified; Rats; Tumor Necrosis Factor-alpha; PPAR alfa; Animals; Adipose Tissue, Brown; C-Reactive Protein